2013
DOI: 10.1016/j.gca.2012.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical evidence of mantle reservoir evolution during progressive rifting along the western Afar margin

Abstract: evidence of mantle reservoir evolution during progressive rifting along the western Afar margin. Geochimica et Cosmochimica Acta, Elsevier, 2013Elsevier, , 102, pp.65-88. 10.1016Elsevier, /j.gca.2012 Geochemical evidence of mantle reservoir evolution during progressive rifting along the western Afar margin AbstractThe Afar triple junction, where the Red Sea, Gulf of Aden and African Rift System extension zones converge, is a pivotal domain for the study of continental-to-oceanic rift evolution. The western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 102 publications
(239 reference statements)
2
48
0
2
Order By: Relevance
“…A recent study [Rooney et al, 2012a] suggest that Hf-Pb data from the Asal Rift have affinity to, and overlap with, the East Sheba Ridge (Aden Ridge) data and has also Indian Ocean-like Hf and Pb isotope signatures [Rooney et al, 2012a]. However it has been also shown that these lava flows exhibit values consistent with mixing between Afar plume and regional lithospheric mantle [Schilling et al, 1992;Rooney et al, 2012a;Rooney et al, 2013]]. In the Afar depression, the isotopic signature of a mantle plume is most pronounced toward Djibouti [Schilling et al, 1992;Rooney et al, 2012a], consistent with maximum temperature values recorded in this area [Rooney et al, 2012b].…”
Section: Crustal Contamination and Source Heterogeneitymentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study [Rooney et al, 2012a] suggest that Hf-Pb data from the Asal Rift have affinity to, and overlap with, the East Sheba Ridge (Aden Ridge) data and has also Indian Ocean-like Hf and Pb isotope signatures [Rooney et al, 2012a]. However it has been also shown that these lava flows exhibit values consistent with mixing between Afar plume and regional lithospheric mantle [Schilling et al, 1992;Rooney et al, 2012a;Rooney et al, 2013]]. In the Afar depression, the isotopic signature of a mantle plume is most pronounced toward Djibouti [Schilling et al, 1992;Rooney et al, 2012a], consistent with maximum temperature values recorded in this area [Rooney et al, 2012b].…”
Section: Crustal Contamination and Source Heterogeneitymentioning
confidence: 99%
“…[45] However, trace element patterns ( Figure 5) and isotopic compositions [Rooney et al, 2012a;Rooney et al, 2013] show that the Asal Rift lava derived from a fertile source. Because the fertile mantle starts melting deeper and melts more, the calculated final pressures of melting slightly decrease, and the initial pressures and crust thicknesses slightly increase compared to a normal mantle composition.…”
Section: Mantle Melting Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 -mantle sequence and average composition points of the mantle (N-MORB, E-MORB, OIB) and crustal (UCC and LCC, Late and lower continental types of crust, correspondingly) sources; RSRRed Sea Rift [Rogers, 1993;Volker et al, 1997]; EAR -East African Rift [Deniel et al, 1994;Duffield et al, 1997;Barrat et al, 1998;Lowenstern et al, 2006;Daoud et al, 2010;Teklay et al, 2010;Field et al, 2012;Rooney et al, 2013]; 2 -sill-and-dike swarms; 3 -amphibolites (metabasallts) of the Nazyam mountains. Letters in circles mean the average compositions of basalts of Ai (A) and Mashak (M) formations, trachybasalts of the Sibirka deposit (S).…”
Section: Discussion Interpretation Of Geochemical and Isotope Data mentioning
confidence: 99%
“…1 -мантийная последовательность и точки средних составов мантийных (N-MORB, E-MORB, OIB) и коровых (UCC и LCC, верхняя и нижняя континентальная кора, соответственно) источников; RSR -Красноморский рифт [Rogers, 1993;Volker et al, 1997]; EAR -Восточно-Африканский рифт [Deniel et al, 1994;Duffield et al, 1997;Barrat et al, 1998;Lowenstern et al, 2006;Daoud et al, 2010;Teklay et al, 2010;Field et al, 2012;Rooney et al, 2013]; 2 -силлово-дайковые рои; 3 -амфиболи-ты (метабазальты) назямских гор. Буквы в кружках -сред-ние составы базальтов айской (А) и машакской (M) свит, трахибазальтов месторождения Сибирка (S).…”
Section: Discussion Interpretation Of Geochemical and Isotope Data unclassified